Hydrolysis and Oxidation of Recalcitrant Substrates by Microbial Isolates from Hot Springs - Anastasiya I. Dmitrieva; Elizaveta R. Faskhutdinova; Timothy A. Larichev; Natalia S. Velichkovich; Veronika Yu. Boger; Larisa M. Aksenova (Техника и технология пищевых производств)
Traditional energy sources pollute the environment. Microbial fuel cells are an alternative energy source that can reduce the environmental burden. Microbial fuel cells also remove recalcitrant wastes from wastewater. This research featured the enzymatic potential of microbial isolates obtained from the Abakan Arzhan thermal spring. The study involved isolates of the genera Geobacter, Thermomonas, and Rhodopseudomonas. The keratinolytic analysis was in line with State Standard R 55987-2014. The chitinolytic activity was determined by injecting a bacterial suspension on Petri dishes with a chitin-containing medium. The lipolytic analysis involved cultivating the isolates in Stern’s glycerol fuchsin broth. The xylan hydrolysis depended on the reducing sugars. The cellulase activity was measured according to the standard method recommended by the International Union of Pure and Applied Chemistry (IUPAC). The catalase potential was evaluated by the gasometric method on 1% gasoline media. The optimal parameters of consortium cultivation were determined by the voltage generated. The Geobacter isolate had the maximal keratinolytic activity while the Thermomonas isolate demonstrated the maximal protein hydrolysis (80.1 ± 1.5%). Both Geobacter and Rhodopseudomonas showed good lytic activity against chitin with the lysis zone of ≥ 3 mm. The Geobacter isolate demonstrated as many as 350 units of xylanase activity and 365 units of cellulase activity; Thermomonas had 350 units of xylanase activity and 360 units of cellulase activity; Rhodopseudomonas showed 310 units of xylanase activity and 304 units of cellulase activity. The maximal catalase properties belonged to Geobacter (1.40 units) and Thermomonas (1.38 units). The maximal energy generation by bacterial consortia occurred at pH 8 and 45°C after 48 h of cultivation. In this research, isolates of the genera Geobacter, Thermomonas, and Rhodopseudomonas from the Abakan Arzhan thermal spring were able to remove recalcitrant components, thus demonstrating good prospects for biological treatment of industrial wastewater.